2020
DOI: 10.1213/ane.0000000000004422
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Coagulation by Thromboelastography During Ongoing Postpartum Hemorrhage: A Retrospective Cohort Analysis

Abstract: BACKGROUND: Rapid assessment of hemostasis during postpartum hemorrhage (PPH) is essential to allow characterization of coagulopathy, to estimate bleeding severity, and to improve outcome. Point of care (POC) coagulation monitors could be of great interest for early diagnosis and treatment of coagulation disorders in PPH. METHODS: Women with ongoing PPH >500 mL who clinically required an assessment of coagulation with thromboelastography (TEG) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…The use of TEG and ROTEM in the identification of hypocoagulopathy and guiding BCT/HAT in PPH is rising in popularity. Only recently have TEG and ROTEM been increasingly studied within the context of PPH [2,3,21,25,[52][53][54][55]58,59,[74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. BCT/HAT can be tailored to this patient population's specific needs using TEG or ROTEM parameters.…”
Section: The Use Of Vhas To Guide Bct and Hemostatic Adjunct Therapy In Pphmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of TEG and ROTEM in the identification of hypocoagulopathy and guiding BCT/HAT in PPH is rising in popularity. Only recently have TEG and ROTEM been increasingly studied within the context of PPH [2,3,21,25,[52][53][54][55]58,59,[74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. BCT/HAT can be tailored to this patient population's specific needs using TEG or ROTEM parameters.…”
Section: The Use Of Vhas To Guide Bct and Hemostatic Adjunct Therapy In Pphmentioning
confidence: 99%
“…Physiologic postpartum hemostasis of placental blood flow depends greatly upon adequate myometrial contraction and mechanical compression of the spiral arteries. Uterine atony is the failure of this physiologic myometrial contraction in the immediate postpartum period and is the most common cause of PPH [2,3,9,15,25,70,74,134,135]. Risk factors for uterine atony include multiparity, multiple gestation, history of PPH, prolonged labor, and placenta previa [70,102].…”
Section: Specific Pathological Entities In Pph 41 Uterine Atonymentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 In postpartum hemorrhage, TEG variables have been compared to traditional laboratory assays. Rigouzzo et al 20 found that the TEG provided rapid detection of hypofibrinogenemia and thrombocytopenia. Algorithms for obstetric care with viscoelastic testing have also been described.…”
Section: Postpartum Hemorrhage Managementmentioning
confidence: 99%